Respon Pertumbuhan Dan Produksi Beberapa Varietas Kedelai Hitam (Glycine max L.) Berdasarkan Ukuran Biji - Rizki Aulia; Rosmayati Rosmayati; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2014)
The objectives of this research was to produce the large seed size of several black soybean varietiesselected based on seed size. The research was conducted on Pasar 1 Tanjung Sari, District MedanSelayang, Medan with a height of ± 25 meter above sea levelon. It was started on Februari until Mei2013 by using Split Plot Design of Two Factors which are varieties and seed size with 4replications. Varieties was researched are Detam1, Detam2, Cikuray and Mallika. The seed sizewas researched are large seed size and small seed size. The result showed that Mallika varietiesshowed the best growth on plant height (34,85 cm) and number of branches on main branches (4,33branches ). The highest production is Detam1 (32,65 g) in production per plant parameter. Theplants from the large seed size showed the best growth on plant height (31,91 cm) and number ofbranches (3,88 branches). The plants from the small seed size produced more medium seed sizewith range 41.92 % - 58.88 %. The plants from the large seed size produced more medium seed sizewith range 41.07 % - 51.55 % except on Detam 2 which from the large seed size produced morelarge seed size. Interaction between varieties and seed size that showed the best growth is oninteraction between Detam 2 varieties with large seed size (V2U2) on plant height parameter (20,35cm). interaction between Detam 1 with small seed size (V1U1) showed the best productioncompare with the others on production per plot (535 g).Key words : black soybean, varieties, seed size